Mechanisms of the sperm guidance, an essential aid for meeting the oocyte - Lottero Leconte, Raquel (2017)
In mammals, ejaculated spermatozoa must migrate into the female reproductive tract in order to reach and fertilize the oocyte (Figure 1). The number of spermatozoa that reach the oviductal isthmus (where they attach to oviductal cells and form the sperm reservoir) is small (1,2) and only ~10% of these spermatozoa in humans become capacitated (3) and acquire a state of readiness for fertilizing the oocyte. In addition, the sperm cells have a torturous and long way between the reservoir and the oocyte at the fertilization site (3–5 cm in humans) (2). These facts, together with the tiny dimensions of the gametes in comparison to the tube length make improbable the sperm arrival to the fertilization site and make evident the need for sperm guidance (4). Different guidance mechanisms appear essential for successful sperm arrival to the fertilization site: the short range mechanism such as chemotaxis (swimming up a chemoattractant gradient) (5) and the long range mechanisms such as rheotaxis (swimming against a fluid flow) and thermotaxis (the temperature-oriented cell motility).